Regional Solutions to Regional Problems: The Elusive Search for Security in the African Great Lakes - Uvin, Peter; Bourque, Andre; Cohen, Craig (Tufts Archival Research Center, 2005)
Volume 29, Issue 2. Summer Peter Uvin, Andre Bourque, and Craig Cohen argue that national programs fail to address the complex dynamics undermining security in the Great Lakes region. Instead, a regional approach must be implemented if peace is to be established for good.